Diffusion-controlled and replacement microtextures in alkali feldspars from two pegmatites: Perth, Ontario and Keystone, South Dakota. (1st December 2015) - Lee, Martin; Parsons, Ian
Macro- and micro-perthitic microclines from pegmatites from Perth, Ontario (Wards catalogue 46 E 0510) and Keystone, South Dakota (Wards 46 E 5125) have been studied using light and electron microscopy. A sample of the type perthite from Perth, Ontario (Hunterian Museum, Glasgow, M2361) was compared using light microscopy. It differs in bulk composition and microtexture from the Wards sample. The Perth sample from Wards is a mesoperthite, with sub-periodic ∼mm-thick albite veins near (100), with irregular surfaces. The microcline has regular tartan twins and formed from orthoclase by a continuous process. The Keystone sample is a microperthite, with non-periodic albite veins mainly in {110}. Irregular tartan twins, volumes of irregular microcline and subgrains suggest that the microcline formed by dissolution–reprecipitation. Microcline in both samples contains semicoherent cryptoperthitic albite films that formed after the development of tartan twins. The bulk compositions of these intergrowths imply exsolution below ∼400°C. Diffusion parameters imply sustained heating for between 0.11 My at 400°C, 1.5 GPa and 8.4 My at 300°C, 1 GPa. Unrealistic times are required at 200°C. Subsequently, the crystals reacted with a fluid leading to replacive growth of the vein perthites. Unusually, Albite twin composition planes in replacive subgrains have sub-periodic dislocations, formed by coalescence of advancing growth twins. Processes that might lead to periodic, replacive intergrowths are discussed. The Perth and Keystone feldspars have been used for experimental work on dissolution during weathering and on anomalous thermoluminescence fading. Their microtextures make them unsuitable for obtaining properties that can be extrapolated to feldspars in general.